Lymphocyte Counts are Dynamic and Associated with Survival after Transcatheter Aortic Valve Replacement. Issue 6 (2nd November 2018) - Al-Kindi, Sadeer G.; Attizzani, Guilherme F.; Decicco, Anthony E.; Alkhalil, Ahmad; Nmai, Chris; Longenecker, Chris T.; Parikh, Sahil; Lederman, Michael M.; Dalton, Jarrod; Zidar, David A.
ABSTRACT: Objective: We sought to determine whether levels of individual leukocyte subsets (neutrophils, monocytes, and lymphocytes) and their post-procedural trajectory are related to survival after transcatheter aortic valve replacement (TAVR). Methods: We conducted a retrospective study of consecutive patients undergoing transfemoral TAVR in a large academic referral center (2012–2014). The association between baseline and 1-day post-TAVR change in leukocyte subsets and mortality were analyzed using Cox proportional hazards and Kaplan-Meier methods. Results: A total of 136 patients were included in this study. Overall, TAVR was associated with a modest increase in total leukocyte counts which was driven by increases in neutrophils and monocytes. In contrast, absolute lymphocyte counts (ALC) decreased sharply after TAVR (median difference −0.43 × 10 9 /L, p < 0.001). The magnitude of this change in ALC did not correlate with the post-procedural neutrophilia or monocytosis. Baseline neutrophil and monocyte counts were not associated with mortality whereas a higher ALC before TAVR was strongly associated with decreased mortality independent of age, gender, or Society of Thoracic Surgeons (STS) risk score (STS-adjusted HR: 0.40 [0.21–0.77] per 10 9 /L, p = 0.006). Conclusions: Patients with diminished lymphocyte counts prior to TAVR may represent a previously unrecognized high-risk population with reduced long-term survival after TAVR. Additional study is needed to determine the role of immune status in patients referred for TAVR and whether the risk associated with limited immunologic reserve is modifiable.